2014
DOI: 10.1007/s10897-014-9786-4
|View full text |Cite
|
Sign up to set email alerts
|

Congruence‐Incongruence Patterns in Alpha‐1 Antitrypsin Deficiency Couples’ Genetic Determinist Beliefs and Perceived Control over Genes: Implications for Clinical and Public Health Genomic Communication

Abstract: Genomics makes possible the isolation of multiple genes as co-factors that increase, but do not determine, risk for many adult-onset medical conditions, including alpha-1 antitrypsin deficiency (AATD). Those diagnosed with an adult-onset medical condition, such as AATD, are often married and make decisions about testing and care as a couple. We examined genetic essentialist and threat beliefs, focusing on beliefs about the genetic contribution to disease susceptibility and severity, as well as perceptions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…In general, essentialism “guides our perceptions by allowing us to sort characteristics into groups and act based on our beliefs about the essence of a category” (Parrott, Smith, Hong, & Worthington, 2015, p. 533). Genetic essentialism places primacy on genes as determining one’s personality, behavior, health, and life course.…”
Section: Genetic Essentialismmentioning
confidence: 99%
“…In general, essentialism “guides our perceptions by allowing us to sort characteristics into groups and act based on our beliefs about the essence of a category” (Parrott, Smith, Hong, & Worthington, 2015, p. 533). Genetic essentialism places primacy on genes as determining one’s personality, behavior, health, and life course.…”
Section: Genetic Essentialismmentioning
confidence: 99%
“…Spouses may have differed in their perceptions of how well a genetic-based health condition could be prevented, which actions to enact and how quickly, and who is responsible for taking action. Married adults differ in the extent to which they believe that lifestyle choices can shape whether genes determine future health (Parrott, Smith, Hong, & Worthington, 2015). Moreover, one protective action for AATD is to avoid environmental toxins, such as quitting smoking and avoiding air pollution (Klitzman, 2009), which can require major lifestyle changes that evoke conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, married individuals do not always share the same beliefs regarding genetics. For example, Parrott, Smith, Hong, and Worthington (2015) found that individuals diagnosed with AATD perceived lower control over genes’ influence on health and higher genetic influence on disease severity when compared to their spouses. Spousal differences in perceptions of unpredictability regarding a genetic diagnosis may thus differ, with the potential for these differences to then impact the outcomes of patients’ perceptions of unpredictability in terms of negative affect and affect-management coping.…”
Section: Discussionmentioning
confidence: 99%